Cossacks in the Civil War: peculiarities of the Ural Cossack host’s participation - A. A. Paderin (Vestnik MGIMO-Universiteta)
This article is about the Cossacks’ participation in the Civil War, which ended 90 years ago. The author focuses on the Ural Cossack host, which represented a unique socio-economic phenomenon. In the article we can see that weighty objective reasons were impelled the Ural Cossacks to an uncompromising armed opposition with the Soviet power: their economic, political and moral values were incompatible with those rules, which the power inculcated by compulsion.